The relationship between high school sociology teacher involvement in the MGMP and teacher's work commitment with its performance - Zubaida, Siti; Hidayat, Sholeh; Faturohman, Nandang (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
This study aims to analyze and describe the relationship between the involvement of SMA sociology subject teachers in the subject teacher conference (X1) with performance (Y), work commitment (X2) with teacher performance sociology (Y) and describe and analyze relationships involvement of high school sociology subject teachers in subject teacher conference (X1) and work commitment (X2) together with performance (Y) in Serang Regency High School, Banten Province, Indonesia. The method used in this study is a quantitative method that aims to reveal the relationship between high school sociology subject teacher involvement in subject teacher conference (X1) and work commitment (X2) with their performance (Y) in SMA Serang Regency. Data was collected using a questionnaire. Analysis of the data used is an analysis of multiple correlations. The results of the study show: First, there is a positive and significant relationship between Teacher Involvement in the subject teacher conference and the performance of high school sociology teachers in Serang Regency . This is shown by testing the correlation coefficient between X1 and Y; the rcount value is 0.764. Second, there is a positive and significant relationship between teacher work commitment and the performance of subject teacher conference sociology teachers. This is indicated by the rcount value of 0.726. Third, there is a positive and significant relationship between teacher involvement in subject teacher conference and teacher commitment and the performance of high school sociology teachers in Serang Regency, with a correlation value of 0.764. This is shown through the calculated F value of 21.69.